2015
DOI: 10.24288/jttr.202825
|View full text |Cite
|
Sign up to set email alerts
|

Üniversite gençliğinin sportif rekreasyon etkinliklerine yönelik ilgileri ve katılma düzeylerinin belirlenmesi

Abstract: Dynamic tempo, monotonous life aiming at branching and insufficient physical activity depending on technology have been one of the biggest problems of people and societies of today.In solving the inactivity problems at issue,it is important for the children and the young to be physically educated in order to make them cope with their problems.In this respect,our aim is to determine the interest and attendance level of university youth in the recreation activities of sports in terms of presenting analytical sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 2 publications
0
2
0
3
Order By: Relevance
“…The findings reported in the literature indicate that most of the university students had the habit of doing sport in their past lives (Ergül et al, 2015). In the current study, it was found that the state of having done sport in the past may have significant effects on their current attitudes towards sport.…”
Section: Discussionmentioning
confidence: 50%
“…The findings reported in the literature indicate that most of the university students had the habit of doing sport in their past lives (Ergül et al, 2015). In the current study, it was found that the state of having done sport in the past may have significant effects on their current attitudes towards sport.…”
Section: Discussionmentioning
confidence: 50%
“…Female students' viewing facilities/services and accessibility sub dimension as a constraint can be explained with the thoughts that they will feel under pressure in case of doing activities with men due to social structure and they will have more difficulties in accessing and using facilities when compared with men. Ergül (2008) stated that presence of sports facilities in the neighborhood students live is a factor that increases the possibility of doing sports. At the same time, it can be said that women's appearances can restrict the activities they participate in public facilities.…”
Section: Discussion and Resultsmentioning
confidence: 99%
“…Süzer (2000), üniversite öğrencilerinin boş zamanlarını değerlendirme üzerine yaptığı çalışmasında, erkek öğrencilerin kız öğrencilere oranla sprotif faaliyetlere daha aktif olarak katıldıklarını tespit etmiştir. Ergül (2008), üniversite gençliğinin sportif rekreasyon etkinliklerine yönelik ilgileri ve katılım düzeyleri üzerine yaptığı çalışmasında ise erkek öğrencilerin kadın öğrencilere göre spor yapmaya daha eğimli oldukları tespit edilmiştir. Bu bağlamda birçok fiziksel aktivitenin kadınlar tarafından tercih edilememesinin temel sebepleri arasında, fiziksel yapılarının erkeklerin fiziksel yapısından daha zayıf olması, boş zaman aktivitelerine katılım için ailelerinden yeterli desteği alamamaları ve yeterli boş zamanlarının olmaması olarak sıralanabilir.…”
Section: Tablo 3algılanan Wellness Ve Boş Zaman Katılımın Cinsiyet Açısından İncelenmesiunclassified